Assessment of elastic models in supercooled water: A molecular dynamics study with the TIP4P/2005f force field - Guillaud, Emmanuel; Joly, Laurent; de Ligny, Dominique; Merabia, Samy (Journal of Chemical Physics, 2017)
Glass formers exhibit a viscoelastic behavior: at the laboratory time scale, they behave like (glassy) solids at low temperatures and like liquids at high temperatures. Based on this observation, elastic models relate the long time supercooled dynamics to short time elastic properties of the supercooled liquid. In the present work, we assess the validity of elastic models for the shear viscosity and the alpha-relaxation time of supercooled water, using molecular dynamics simulations with the TIP4P/2005f force field over a wide range of temperatures. We show that elastic models provide a good description of supercooled water dynamics. For the viscosity, two different regimes are observed and the crossover temperature is found to be close to the one where the Stokes-Einstein relation starts to be violated. Our simulations show that only shear properties are important to characterize the effective flow activation energy. This study calls for experimental determination of the high frequency elastic properties of water at low temperatures. Published by AIP Publishing.

Decoupling of viscosity and relaxation processes in supercooled water: a molecular dynamics study with the TIP4P/2005f model - Guillaud, Emmanuel; Merabia, Samy; de Ligny, Dominique; Joly, Laurent (Physical Chemistry Chemical Physics, 2017)
During the last few decades, many experimental and numerical studies have tried to understand the special dynamics of water at low temperatures by measuring structural relaxation times or shear viscosity, but their conclusions strongly depended on the chosen observable and on the range of temperatures considered. Moreover, recent work [J. Chem. Phys. 2013, 138, 12A526] showed that viscosity and relaxation times could decouple at low temperature in a model binary mixture, raising questions on their equivalence to study supercooled water. Here we used molecular dynamics simulations with the promising TIP4P/2005f water force field to investigate the behavior of both the shear viscosity and the relaxation times of water in a large range of temperatures, in order to get a consistent picture of the dynamics of supercooled water. We show that the TIP4P/2005f model reproduces accurately the experimental values of both the viscosity and the diffusion coefficient over a very large range of temperatures. Focusing first on the structural relaxation dynamics, we observe a decoupling between the so-called alpha- and beta-relaxation times of water at ca. 350 K, suggesting a supercooled-like dynamics over a very large domain of temperatures. By computing shear viscosity over this domain, we compare the accuracy of several phenomenological laws for low temperature dynamics of water to describe both viscosity and alpha-relaxation time. Unlike what is usually admitted, our tests suggest those quantities are not coupled at low temperatures, and thus should not be considered equivalent. In particular, deviations from the Stokes-Einstein relation appear at lower temperatures for the viscosity than for the alpha-relaxation time. These results open new perspectives to understand the dynamics of supercooled water and show the performance of the TIP4P/2005f force field to characterize it.